2015
DOI: 10.1007/s13346-015-0246-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of anti-malarial bio-conjugates: artesunate-loaded nanoerythrosomes

Abstract: Biodegradable cellular carrier has desired properties for achieving effective long-term controlled release of drugs having short half life. To reduce the undesired effects of drug, advanced drug delivery systems are needed which are based on specific cell targeting module. Artesunate (ART) conjugation on nanoerythrosomes (NE) can have controlled delivery to avoid drug leakage, increase the stability, and reduce cost and toxicities. In this study nanosized lipoprotein membrane vesicles bearing ART were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In vitro studies prove that the nanoerythrosomes are successful prototype to carry loaded cytotoxic agents as anticancer therapy (Désilets et al 2001). It is also reported that nanoerythrosomes, hybrid RBCs was the successful in delivering anti-malarial agents as compared to free drug in the rat model (Agnihotri et al 2015).…”
Section: Hybrid Rbcsmentioning
confidence: 96%
“…In vitro studies prove that the nanoerythrosomes are successful prototype to carry loaded cytotoxic agents as anticancer therapy (Désilets et al 2001). It is also reported that nanoerythrosomes, hybrid RBCs was the successful in delivering anti-malarial agents as compared to free drug in the rat model (Agnihotri et al 2015).…”
Section: Hybrid Rbcsmentioning
confidence: 96%
“…To enhance the anti-tumor effects of Ats, many new techniques were attempted to increase the drug’s distribution in tumor cells or to improve the targeted delivery of drugs into cell organelles to induce cell death [2123]. Nanoparticles (NPs) as a key tool in targeted cancer treatment have been widely investigated, and they have shown promising potential.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, this DDS apparently had not been pursued to the level of systematic studies in vivo , perhaps due to very rapid clearance from blood, as this formulation lost biocompatibility [181]. In one recent study, nanoerythrosomes filled with anti-malarial agents were cleared in rats within a few hours (although slightly slower than free drug) [182]. …”
Section: Rbc-inspired and Rbc-hybrid Nanocarriersmentioning
confidence: 99%